The influence of 8 weeks of endurance training on blood lactate threshold for male handball players - Ramadan, W. A.; Mustafa, R. (Journal of Human Sport & Exercise, 2023)
The blood lactate transfusion activity is characterized by triphasic nature. The required counterbalance between glycolysis and metabolism determines the flow of lactate into the muscles. Exercise (>80% of VO2max) has been observed to elevate the level of glycolysis and the gradual accretion of lactate to steadily higher levels, which consequently leads directly to fatigue. The purpose of this study was to investigate the influence of endurance training on the accumulation of lactate and whether it depends on the intensity of training or not. This study involved Sixteen participants, with mean age; 19.18 ± 1.0 years. Participants were asked to run at four various paces (9 km/h, 10.8 km/h, 12.6 km/h, and 14.4 km/h) for 60 minutes. After each exercise, blood lactate is immediately measured using Accusport and Polar devices. Statistically significant differences were seen in heart rate (HR), blood lactate (BL) and maximum lactate steady state (MLSS) after training (72.64 vs. 61.88), (158.22 vs 133.19), and (13.02 vs 8.41) > .01 respectively. Our results suggest that endurance training for 8 weeks can improve lactate threshold and blood lactate accumulation.